Avaliação pós-ocupação do Museu de Arqueologia da UFMS: Conforto térmico e preservação do acervo - SABRINA LINI (2024)
This study presents an evaluation of the microclimate in the Archaeology Museum of UFMS, focusing on the thermal comfort of employees and the preservation of the collection. The research was conducted on the first floor of the Memorial of Citizenship and Culture Apolônio Carvalho Building, in Campo Grande, MS. The study combined objective measurements of environmental variables with the subjective perception of users, utilizing instruments such as the SENSU - Confortímetro and HOBO® sensors. The measurements indicated that air, globe, radiant, and operative temperatures remained stable throughout the day, reflecting thermal stability. The observed low air velocity suggests the need for ventilation improvements to prevent a sensation of stagnation. Thermal comfort indices, calculated based on Fanger's PMV-PPD model, indicated that occupants experienced a thermal sensation ranging from slightly cool to neutral. Questionnaire responses from employees revealed that, despite some complaints of thermal discomfort due to cold in the early hours, most participants reported feeling comfortable throughout the evaluation period. A comparison of the results with standards highlighted the need for adjustments in ventilation and air conditioning systems to enhance thermal comfort and collection preservation. The implementation of strategies to adjust air conditioning, particularly during periods of extreme temperatures, and the protection from solar radiation at openings are recommended.